BANKRUPTCY PREDICTION ANALYSIS USING THE GROVER AND OHLSON MODELS IN WOOD AND ITS MANAGEMENT SUB-SECTOR COMPANIES THAT ARE LISTED ON THE IDX - Utami, Reni Restriani; Ichwan Musa, Muh.; Anwar, Anwar (Journal of Accounting Research, Utility Finance and Digital Assets, 2022)
This study aims to predict bankruptcy and also to find out the differences in predictions in timber sub-sector companies and their management during 2017-2021 using the Grover and Ohlson models. The type of research used is quantitative research with the research population being wood sub-sector companies and their management listed on the IDX. The sample in the study was PT. SLJ Global Tbk (SULI) and PT. Tirta Mahakam Resources Tbk (TIRT). Data analysis techniques use Grover and Ohlson models.The results showed that by using the Grover PT. SLJ Global Tbk (SULI) in 2018-2021 and PT. Tirta Mahakam Resources Tbk (TIRT) in 2019-2021 is predicted to go bankrupt. Ohlson's own model predicts that in 2017-2021 both companies go bankrupt. Mann Whitney's test results found that there was no difference in predicting the potential bankruptcy of SULI and TIRT using the Grover model with Ohlson.